Ionic Aggregation‐Induced Emission: Ionic Aggregation‐Induced Emission: Bulky Hydrophobic Counterions Light Up Dyes in Polymeric Nanoparticles (Advanced Optical Materials 14/2020). Issue 14 (20th July 2020) - Aparin, Ilya O.; Melnychuk, Nina; Klymchenko, Andrey S.
Abstract : Ionic aggregation‐induced emission (iAIE), described in article number 2000027 by Andrey S. Klymchenko and co‐workers, combines concepts of AIE and bulky hydrophobic counterions to fight aggregation‐caused quenching in cationic weakly emissive dye. The bulky counterions light up flat ionic dyes in the solid state by preventing H‐aggregation and restricting intramolecular rotation. iAIE has been applied for the preparation of bright dye‐loaded polymeric nanoparticles exhibiting ∼50‐fold stronger emission without blinking compared to quantum dots 605 in single‐particle microscopy.